Entry Into Foreign Markets and Developed Countries by Entrepreneurial Firms from Developing Countries - Choudhary, Ankit (2008)
Many studies have been carried out into international market entry; however, these have typically been from the perspective from the Western firms. We know little on the other hand about how firms from Non-Western countries can enter the Western markets, which may in part explain the lack of presence of such products in Western shops. In response, this study examines factors affecting the penetration of Indian products into UK supermarkets. It is found that synchronizing price, quality and brand is critical to developing a compelling value proposition that appeals to UK consumers. This requires considerable adaptation in the product proposition. The work concludes with implications and recommendations for future research for the stakeholders.